Multidisciplinary care in the hematology clinic: Implementation of geriatric oncology. Issue 3 (May 2019) - Goede, Valentin; Stauder, Reinhard
Abstract: Multidisciplinary care is believed to provide benefits to patients with cancer. Tumor board conferences as well aspalliative care or psycho-oncological services have not only become common in oncology, but also in hematology clinics dedicated to the treatment of hematological cancers. Malignant hematological diseases are highly prevalent among older persons. Demographic changes in many countries worldwide are prompting the integration of geriatric principles, methodology, and expertise into existing procedures and infrastructure of multidisciplinary care in hematology clinics. Achieving this goal requires the close collaboration or even incorporation of multiple new professions in the hematology clinic in order to meet the needs of older patients with hematological malignancies who also have comorbidities and functional impairments. We here review the rationale, current evidence, and practical approaches of integrating geriatric oncology into multidisciplinary care in the hematology clinic.